Academic Stress on Structured Internship Students: The Effect of Interpersonal Communication and Friendship Quality - Agustin Erna Fatmasari; Niken Fatimah Nurhayati; Endah Mujiasih; Hidayatun Nur'Aini; Megawati Sekar Langit Cahyaning Nagari (Universitas Ahmad Dahlan, 2024)
The purpose of this study was to examine the effect of parent-child interpersonal communication and friendship quality on academic stress. This study used multiple regression analysis methods with the SPSS version 26.0 program to examine the effect of Parent-Child Interpersonal Communication and Friendship Quality on Academic Stress in Structured Internship Students. A total of 206 participants were selected using non-probality sampling, convenience sampling. Data collection used three research instruments, which are the Academic Stress Scale (alpha= .957), the Parent-Child Interpersonal Communication Scale (alpha = .922), and the Friendship Quality Scale (alpha= .926). All hypotheses of this study can be accepted. There is a significant influence of parent-child interpersonal communication and friendship quality both together and separately on academic stress. The results showed that parent-child interpersonal communication and friendship quality influenced academic stress by 10.3%. Parent-child interpersonal communication on academic stress is 14.5%, and the quality of friendship has an influence of 7.2% on the occurrence of student academic stress.